2012
DOI: 10.1016/j.cplett.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and band gap of uniaxially deformed (6,0) carbon nanotube

Abstract: The atomic and band structures of the (6, 0) zigzag carbon nanotube at its axial elongation are calculated by semiempirical molecular orbital and by tight-binding methods. The ground state of the nanotube is found to have a Kekule structure with four types of bonds and difference between lengths of long and short bonds of about 0.005 nm. The structural phase transition is revealed at ≈ 9% elongation, resulting in a quinoid structure with two types of bonds. This structural phase transition is followed by the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For the selected systems, GLY/G (XY), GLY/CN (YZ), and GLY/MoS 2 (XY) the band gaps have the following values: 1.95, 0.51, and 1.58 eV, respectively. For pristine G, CN (6,0) zigzag and MoS 2 , the band gaps have values of 0 eV, 0.19 eV and 1.8–1.9 eV, respectively. This indicates that for both 2D materials with carbon atoms, band gaps increase (materials adopt a more semiconductor behavior suitable for biosensing applications), in contrast to the MoS 2 band gap which slightly decreases (remains being a semiconductive material suitable for transistors in sensing devices). , …”
Section: Resultsmentioning
confidence: 99%
“…For the selected systems, GLY/G (XY), GLY/CN (YZ), and GLY/MoS 2 (XY) the band gaps have the following values: 1.95, 0.51, and 1.58 eV, respectively. For pristine G, CN (6,0) zigzag and MoS 2 , the band gaps have values of 0 eV, 0.19 eV and 1.8–1.9 eV, respectively. This indicates that for both 2D materials with carbon atoms, band gaps increase (materials adopt a more semiconductor behavior suitable for biosensing applications), in contrast to the MoS 2 band gap which slightly decreases (remains being a semiconductive material suitable for transistors in sensing devices). , …”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the structures of armchair (11,11) nanotube remain intact without any bond breaking within the strain of −8% to 8%, which demonstrates the large elastic range of armchair GeS nanotubes. N. A. Poklonski et al reported that the rst order deformation structure phase transition is revealed at the critical uniaxial elongation 9% for the (6, 0) CNT 57 and 5% for the (5, 5) CNT. 58 It is well known that the puckered structures such as black phosphorus can bear high strain without breaking the structure by changing their puckering angle.…”
Section: Resultsmentioning
confidence: 99%
“…The I-V characteristics and transmission spectrums are acquired by simulating this geometry. The parameters used in the simulation are in accordance with [22][23][24]. The basis set used is double zeta polarized for carbon nanotube and single zeta polarized for both CrO2 electrodes.…”
Section: Simulation Methods and Setupmentioning
confidence: 99%